PEMAHAMAN ATAS KECAKAPAN HIDUP SOSIAL OLEH PARA PENDIDIK PRASEKOLAH DAN PENERAPANNYA - Yulia Ayriza (Jurnal Kependidikan, 2006)
Abstract This research is the first year of multi-year research. It has three main considerations. Firstly, education is something that inseparable from human life and has a very fundamental function in building human attitude. Secondly, social life skill is a very important skill that should be learned and mastered gradually. The research method is survey and using quantitative as well as qualitative approach complementary. The research subjects are from Yogyakarta and Central Java provinces. The research subjects are 161 consist of 105 preschool educators, 50 parents,4 school committee and 4 are officers from the local office of education. The data were analyzed descriptively. The result shows that most of the preschool educators do not comprehend properly on the meaning of social skill, and also do not really realize on how to put into practice in their educating practice preparation. The society especially decision makers in the local office of education have not specifically socialized on the aspects of social skills. Keywords: early childhood educator, and social life skill